Nanowires : complete handbook - Maya Sheikh; Ahamad, Zahra (New Delhi Wordpen Academic Publishing, 2025)
Nanowires of Fe/Mgo/Fe Encapsulates in carbon nanotubes; Daimond Nanowire synthesis properties and applications; Analysis electrochemical and structurally enhanced Limn20 Nanowire cathode system; ZnO Nanowire growth directions and parameters affecting their surface morphology; Nanowires and room temperature mid infrared emission; Parasitic capacitances on scaling lateral Nanowire; Magnetoresistance and structural characterization of electrospum La-Xsrxmno Nanowire networks
Keywords: 9